ANALISIS PROSES SCAFFOLDING PADA PEMBELAJARAN MATEMATIKA DI KELAS VIII SMP NEGERI 4 KARANGANYAR - Nofiansyah, Wahyu; Sujadi, Imam; Kusmayadi, Tri Atmojo (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research was aimed to describe scaffolding process in mathematics learning in the learning material of straight line equation at grade VIII Junior High School Number 4 in Karanganyar Regency in theÂ Academic Year of 2013/2014 for conceptual and procedural knowledge. This research was a descriptive qualitative research. The main subject of this research was a mathematics teacher grade VIII Junior High School Number 4 in Karanganyar Regency. Meanwhile, the minor subject in this research was students getting scaffolding from teachers in the learning process. The selection ofÂ research subject was by purpossive sampling technique. In this research, researcher used passive participation observation and not structured interview recorded by using handycam. In this research, the data validity technique was triangulation technique. The result of research showed as follows. 1) The scaffolding process of learning activities in the learning material of straight line equation for conceptual knowledge given by teacher was to keep students on task, and provide clear direction and reduce students confusion. It was scaffolding process given often by teachers. While the scaffolding process given occasionally by teachers was presenting the conducting questions, clarifies expectations and incorporates assessment, and presented the information clearly. 2) The scaffolding process of learning activities in the learning material of straight line equation for procedural knowledge given by teachers was to present the information clearly and present the conducting questions. It was scaffolding process given often by teachers. While the scaffolding process given occasionally by teachers was directed students against reference, keeps students on task, involved studentâs participation, provides clear direction and reduces studentsâ confusion, and clarifies expectations and incorporates assessment.Keywords: scaffolding, conceptual knowledge, procedural knowledge